Perilaku Phubbing Dalam Kepemimpinan Organisasi Ditinjau Dari Perspektif Islam - Fiza Fradesa; Pit Arzuna; Faisal Ahmadi (Jurnal Manajemen Bisnis Syariah, 2024)
This paper aims to analyze phubbing behavior in organizational leadership from an Islamic perspective. Researchers use this type of library research, namely research that seeks answers to problems through various library information such as books, encyclopedias, journals and other scientific documents. The nature of this research is descriptive analysis, namely regularly describing the data obtained, understood and described so that readers can understand it better. The data used in this research is secondary data. The reseach results show that phubbing behavior has serious impacts, not only detrimental to health but also psychological and even social. Communication within an organization is very important to achieve common goals. A leader is required to have good communication with his members. If a leader engages in phubbing behavior towards his members, it will have an impact on the quality of their work. Leaders who have good communication tend to be able to motivate their members to achieve goals. On the other hand, if a leader tends to ignore his members with phubbing behavior, his members will also be half-hearted in achieving their goals. In Islam it is also recommended to speak kind words and not hurt other people's feelings